Blood cyst of the mitral valve - is it common? Case report - Ioana Ionac; Cristian Mornos; Horea Feier; Alice Dema; Adina Ionac (Sciendo, 2021)
Cardiac blood cysts are benign tumors, usually congenital malformations, found on the endocardium, particularly along the closing lines of the heart valves. Blood cysts of the heart are commonly reported at postmortem findings in infants and they are very rare in adults. We report a case of a 39 year old patient, who was incidentally discovered during echocardiography having a blood cyst attached to the ventricular face of the anterior mitral valve and to the mitral chordae. During surgery, the cystic mass was resected. Mitral valvuloplasty was successfully performed and the patient had an uneventful recovery. Blood cysts are rarely reported, thus there is no consensus or guidelines for the optimal management of the asymptomatic cases. Although our patient was asymptomatic and the cyst did not interfere with the cardiac function, together with the heart team, we chose the surgical resection of the cardiac mass in order to prevent possible complications.